Optimalisasi Sumber Daya Pertanian Melalui Pendekatan Edukasi Berkelanjutan Di Desa Lumansari, Kabupaten Kendal - M. Sultan Alamsyah Nabil Akbar; Alya Faiza; Aulia Rosyida Kusamadewi; Gustaf Faradin Ahsan Abimanyu; Isma Jazilatur Rosidah; Bunga Noer Intan Permatasari; Latif Latif; Mokhamad Iklil Mustofa (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to optimize agricultural resources in Lumansari Village, Kendal Regency, through a sustainable education approach focused on tobacco farmers. Lumansari Village has significant potential in the agricultural sector, particularly in tobacco commodities, but there are still challenges in utilizing resources efficiently and sustainably. This community service program involves training and mentoring tobacco farmers on more modern cultivation techniques, land management, and environmentally friendly farming practices. The results of this program indicate an increase in farmers’ knowledge and skills in managing agricultural resources, which has implications for increased productivity and the sustainability of agricultural enterprises in the village. This sustainable education is expected to serve as a model for other areas with similar characteristics.